Polynomials with integer coefficients and Chebyshev polynomials - Trigub, Roal′d M. (Journal of mathematical sciences (New York, N.Y.), 2017)
The paper is devoted to the popularization of one of the topics at the border between analysis and number theory that is related to polynomial with integer coefficients. Keywords. Extreme properties of polynomials, transfinite diameter, basic theorem for symmetric polynomials, polynomial with integer coefficients polynomial, Minkowski theorem for convex bodies, power of an algebraic number, Eisenstein criterion, asymptotic law of distribution of prime numbers, approximation of functions by polynomial with integer coefficients polynomials and polynomials with natural coefficients, the best approximation of a constant.